2019
DOI: 10.1021/acsami.9b13174
|View full text |Cite
|
Sign up to set email alerts
|

Non-Dendritic Zn Electrodeposition Enabled by Zincophilic Graphene Substrates

Abstract: Rechargeable zinc (Zn) batteries suffer from poor cycling performance that can be attributed to dendrite growth and surface-originated side reactions. Herein, we report that cycling performance of Zn metal anode can be improved significantly by utilizing monolayer graphene (Gr) as the electrodeposition substrate. Utilizing microscopy and X-ray diffraction techniques, we demonstrate that electrodeposited Zn on Gr substrate has a compact, uniform, and nondendritic character. The Gr layer, due to its high lattice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
123
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 140 publications
(129 citation statements)
references
References 72 publications
5
123
0
1
Order By: Relevance
“…3A). The origin of the energy release is manifold-(i) The possible binding between the metal deposit and a "metal-philic" substrate provides a chemical driving force (76), and (ii) the possible difference between surface tensions acts as a physical driving force. It has been argued in many studies that Mg metal does not form dendrites because of its "vanishing small" on January 10, 2021 http://advances.sciencemag.org/ Downloaded from surface diffusion barrier E diff that gives rise to a very large surface diffusivity D s (77).…”
Section: Fluxes Near the Metal Deposition Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…3A). The origin of the energy release is manifold-(i) The possible binding between the metal deposit and a "metal-philic" substrate provides a chemical driving force (76), and (ii) the possible difference between surface tensions acts as a physical driving force. It has been argued in many studies that Mg metal does not form dendrites because of its "vanishing small" on January 10, 2021 http://advances.sciencemag.org/ Downloaded from surface diffusion barrier E diff that gives rise to a very large surface diffusivity D s (77).…”
Section: Fluxes Near the Metal Deposition Interfacementioning
confidence: 99%
“…This heteroepitaxy provides an effective manipulator for regulating the electrodeposition morphology of metals. We showed recently that horizontally aligned graphene layer, which has a  = 7% with Zn, can effectively promote the formation of horizontally aligned, (002)-textured Zn plate-like electrodeposits that claim plating/stripping efficiencies of >99.6% over thousands of cycles (22,76). In the early exploration of a group of powder-based Zn electrodes used in alkaline batteries (140), it has been suggested that the addition of some metal oxides (e.g., PbO or SnO) introduces a similar epitaxial effect (141).…”
Section: Crystallography Of Zinc Metal Electrodepositsmentioning
confidence: 99%
“…[ 64–68 ] Cu foil coated with monolayer graphene (Gr) via chemical vapor deposition (CVD) is shown as an effective approach to control crystal growth behavior of Zn. [ 69 ] As shown by SEM and X‐ray powder diffraction (XRD) analyses in Figure , the electrochemically platted Zn is grown in the (001) direction parallel to the Gr‐modified electrode surface. Density‐functional theory (DFT) calculations (Figure 11f‐j) show that Gr layer shows a high affinity toward Zn and can serve as a zincophilic substrate by absorbing Zn 2+ ions to the inherent defect sites of Gr.…”
Section: Strategies To Suppress Zn Dendrite and Parasitic Side Reactionsmentioning
confidence: 99%
“…The modification strategies for Zn-metal anodes are similar to those of alkali-metal anodes. Up to now, a great deal of strategies have been proposed, such as constructing 3D current collectors, [121][122][123] providing a host for the "hostless" Zn anode, [124][125][126] modifying liquid electrolytes, [127][128][129] utilizing solid-state electrolytes, [130][131][132] alloy engineering, [133] using zincophilic substrates, [134] interfacial design, [135][136][137] adding seeds to regulate Zn deposition, [138] and designing multifunctional separators. [139]…”
Section: Modification Strategies For Zn-metal Anodesmentioning
confidence: 99%